Analysis of the biological structures stimulation by electrical impulses - Волков, С. І.; Бульба, Є. М.; Смердова, Т. А. (Scientific Progress & Innovations, 2012)
A model is proposed and analyzed the electrical properties of biological tissues, which takes into account the complex impedance of a living system and the polarization of cell membranes due to the work of ion pumps. The differential equation that relates the excitation voltage with the AC frequency current and allows a theoretical basis for the law of the time of stimulation. Based on the proposed model, we consider the cases of irritation for the rectangular pulse and sinusoidal AC input voltage.